Natural Resources and Environment Management for the Development of Local Wisdom - Yuliana, Evi; Yusuf, Maulana; Nirmalasary, Try Nensy; Amri, Nanda Hasanul; Erlyn, Putri; Hariani, Poedji Loekitowati; Hidayat, Bachtari Alam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Natural resources are environmental components that include biological and non-biological resources that work together to produce an ecosystem. Rivers are one of the natural resources that sustain life. Musi River is a 750-kilometer-long river in the Indonesian state of South Sumatra. Rivers are an integral aspect of the environment and natural resources that must be protected in order for humanity to survive. Natural resources have the potential to be a source of local wisdom development. The objective of this research is to gain an understanding of how natural resources and the environment are managed in order to foster the development of indigenous wisdom. The purpose of this study is to define and analyze the opportunities, challenges, strengths, and weaknesses associated with natural resource management and the development of indigenous knowledge in Palembang. Palembang's natural resources, particularly its rivers, have the potential to have a positive impact on the environment and the development of indigenous wisdom if managed optimally. Ecological awareness is critical for the people of Palembang in managing the potential of natural resources for the development of local knowledge, such as maintaining the river's purity and keeping the fauna that is a source of local wisdom.